The effects of toothpaste amounts and post-brushing rinsing methods on salivary fluoride retention - Kanyapak Sotthipoka; Pintusorn Thanomsuk; Rungroj Prasopsuk; Chutima Trairatvorakul; Kasekarn Kasevayuth (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to investigate the salivary fluoride retention as fluoride concentration, amount of soluble fluoride, half-life (t1/2) and salivary flow rate of different amounts of toothpaste and rinsing procedures. Design/methodology/approach - A randomized crossover study of 21 healthy volunteers was designed to compare pharmacokinetic parameters of 1 g (B1) and 0.3 g (B0.3) of toothpaste without rinsing and brushing with 1 g of toothpaste with expectoration followed by water rinsing (B1R). Unstimulated saliva was collected before brushing as a baseline and at 0, 5, 10, 30, 60 and 90 min after the completion of the tooth brushing procedure. Findings - The salivary fluoride concentration and amount of soluble fluoride of the B1 group were significantly higher than the B0.3 and B1R groups. The B1 and B1R groups prolonged the remineralizing level up to 60 min while the B0.3 group retained their remineralizing levels for 30 min. The initial t1/2 (rapid phase) of B1 and B1R groups were significantly longer than the B0.3 group. The late t1/2 (slow phase) of the B0.3 group was significantly longer than the B1 group. This is called the two-compartment open pharmacokinetics model. There was no statistical difference of salivary flow rates between all groups. Originality/value - Non-rinsing and the amount of fluoride toothpaste play an important role in raising salivary fluoride levels and prolonging the remineralizing level of the oral cavity.